Serotype distribution and antimicrobial susceptibility of Streptococcus pneumoniae associated with invasive pneumococcal disease among adults in Japan. (January 2021) - Yanagihara, Katsunori; Kosai, Kosuke; Mikamo, Hiroshige; Mukae, Hiroshi; Takesue, Yoshio; Abe, Machiko; Taniguchi, Kazuko; Petigara, Tanaz; Kaku, Mitsuo
Highlights: S. pneumoniae isolates were collected from adults with invasive pneumococcal disease (IPD) in Japan. Prevalence of invasive pneumococcal disease caused by PPV23 serotypes was 61%. Low prevalence of invasive pneumococcal disease caused by PCV7 and PCV13 serotypes. Non-vaccine serotypes accounted for 37.9% of all isolates. Improved vaccination rates and next-generation vaccines are warranted in Japan. Abstract: Objectives: This study evaluated the serotype distribution and antimicrobial susceptibility of Streptococcus pneumoniae isolates from adults (aged ≥20 years) with invasive pneumococcal disease (IPD) in Japan. Methods: This prospective observational study was conducted in 49 participating Japanese hospitals. S. pneumoniae isolates were serotyped and tested for antimicrobial susceptibility at a central laboratory. Information regarding patient characteristics, underlying disease, IPD clinical syndromes, and treatment was collected through medical chart review. Results: The final analysis included 177 patients enrolled from 45 hospitals between September 2016 and April 2018 (bacteraemic pneumonia, 110; bacteraemia without identified focus, 29; meningitis, 19). Most patients (70.1%) were aged ≥65 years and most had underlying disease (79.1%). The proportion of isolates from serotypes contained in the pneumococcal polysaccharide vaccine (PPV) 23 was 61.0%, while those in the pneumococcal conjugate vaccine (PCV) 7 and PCV13 were 2.8% and 28.2%, respectively. Non-vaccine serotypes accounted for 37.9% of all isolates and 50.8% of isolates from immunosuppressed patients. Serotype 12F was the most common vaccine serotype, followed by serotype 3. Conclusions: The continued disease burden of IPD in adults in Japan warrants improved vaccination rates and development of next-generation vaccines that include serotypes not currently covered. Clinical trial registration: Clinical trial summary registration number 160, 822, 918, 146; JapicCTI-163352.